Pancreatic Siphon: A Major Determinant of Selective Shunts. Is it a Historical Entity now? - Rajvilas Anil Narkhede; Snehal Ashok Naphade (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Surgical management of portal hypertension has changed according to time, evolving from just complete shunts to selective shunts and to liver transplantation. The outcomes also greatly improved owing to better understanding of portal hemodynamics and disease nature. Introduction of selective shunts showed promising results just to be challenged by poor outcome with development of "pancreatic siphon" which then studies in detail. This intra-pancreatic and peri-pancreatic collateral veins which connected portal and splenic veins formed basis of systemic loss of portal flow and thus ending up in failure of selectivity. Pancreatic siphon was found to be associated with increased rates of hepatic encephalopathy post selective shunting along with increased rates of hepatic failure. In addition to this pancreatic siphon led to metabolic sequel like new onset of diabetes, ischemic or compressive pancreatic ductopathy and intrapancreaic cholangiopathy. Although the shunting procedures are not that commonly done, pancreatic siphon has moved out of the limelight. It was just an attempt of recapping the existence of an unfamiliar entity forming delicate balance in the portal circulation.